Manipulating perfume delivery to the interface using polymer-surfactant interactions. - Bradbury, R; Penfold, J; Thomas, R; Tucker, I; Petkov, J; Jones, C (Elsevier, 2015)
Enhanced delivery of perfumes to interfaces is an important element of their effectiveness in a range of home and personal care products. The role of polyelectrolyte-surfactant mixtures to promote perfume adsorption at interfaces is explored here. Neutron reflectivity, NR, was used to quantify the adsorption of the model perfumes phenylethanol, PE, and linalool, LL, at the air-water interface in the presence of the anionic surfactant sodium dodecylsulfate, SDS, and the cationic polyelectrolytes, poly(dimethyldiallyl ammonium chloride), polydmdaac, and poly(ethyleneimine), PEI. The strong SDS-polydmdaac interaction dominates the surface adsorption in SDS-polymer-perfume (PE, LL) mixtures, such that the PE and LL adsorption is greatly suppressed. For PEI-SDS-perfume mixtures the PEI-LL interaction competes with the SDS-PEI interaction at all pH at the surface and significant LL adsorption occurs, whereas for PE the PEI-SDS interaction dominates and the PE adsorption is greatly reduced. The use of the strong surface polyelectrolyte-ionic surfactant interaction to manipulate perfume adsorption at the air-water interface has been demonstrated. In particular the results show how the competition between polyelectrolyte, surfactant and perfume interactions at the surface and in solution affect the partitioning of perfumes to the surface.